Melancholy as a Source of Creative: a Paradox in Heidegger's Thought - Rifqi Khairul Anam (Fakultas Teologi, Universitas Sanata Dharma, 2025)
This paper explores the paradoxical relationship between melancholy and creativity within the framework of Heideggerian philosophy. Building upon the notion that melancholy is not merely a psychological state but a fundamental mode of being, it argues that this condition, characterized by an awareness of human finitude and the limitations of existence, serves as a crucial catalyst for creative activity. Following Heidegger, the paper posits that true freedom, the cornerstone of creative expression, is inextricably linked to a sense of burden and responsibility, giving rise to a melancholic mood. This melancholic contemplation, while seemingly negative, provides the fertile ground for artistic and intellectual innovation. The paper analyzes how this interplay between melancholic awareness and the creative impulse manifests in various forms of human expression, from artistic creation to philosophical inquiry. By examining the act of creation as a confrontation with